Integrated use of plant growth-promoting bacteria and nano-zinc foliar spray is a sustainable approach for wheat biofortification, yield, and zinc use efficiency - Jalal, Arshad; Oliveira, Carlos Eduardo da Silva; Fernandes, Guilherme Carlos; da Silva, Edson Cabral; da Costa, Kaway Nunes; de Souza, Jeferson Silva; Leite, Gabriel da Silva; Biagini, Antonio Leonardo Campos; Galindo, Fernando Shintate; Teixeira Filho, Marcelo Carvalho Minhoto (Frontiers in Plant Science, 2023)
The intensive cropping system to pursue high grain production has disturbed agricultural sustainability and nutritious security due to the imbalance use of chemical fertilizers. Plant growth-promoting bacteria (PGPBs) could be one of the sustainable strategies to improve nutrient acquisition and uptake in edible tissues of wheat to combat Zn malnutrition and hidden hunger. Therefore, the objective was to determine the best performing PGPBs inoculant with nano-Zn foliar application on growth, grain yield, concentration of Zn in shoot and grains, Zn use efficiencies and Zn intake under cultivation of wheat in tropical savannah of Brazil. The treatments consisted of four PGPBs inoculations (without inoculation, Azospirillum brasilense, Bacillus subtilis, and Pseudomonas fluorescens) and five Zn doses (0, 0.75, 1.5, 3 and 6 kg ha−1). Inoculation of B. subtilis and P. fluorescens in combination with 1.5 kg ha−1 foliar nano-Zn fertilization increased concentration of Zn, nitrogen and phosphorous in shoot and grain of wheat. Grain yield of wheat was increased with increasing nano-Zn spray up to 5 kg Zn ha−1 under inoculation of A. brasilense in 2019, while foliar nano-Zn up to a dose of 1.5 kg ha−1 along with inoculation of P. fluorescens in 2020 cropping season. Shoot Zn accumulation was improved by 30 and 51% with inoculation of P. fluorescens in 2019 and 2020 crop seasons. Zinc partitioning index was increased with increasing nano Zn foliar fertilization up to 3 kg ha−1 and inoculation with P. fluorescens. Zinc use efficiency was increased with increasing nano-Zn foliar up to 3.3, 1.8 and 3.0 kg ha−1 and 3.6, 2.8 and 2.8 kg ha−1 along with inoculation of A. brasilense, B. subtilis and P. fluorescens in first and second wheat cropping season, respectively. Applied Zn recovery was increased with increasing nano-Zn foliar up to 3.18, 3.12 and 3.05 kg ha−1 in 2019 and 3.25, 3.06 and 3.06 kg ha−1 in 2020 along with inoculation of A. brasilense, B. subtilis and P. fluorescens, respectively. Therefore, inoculation of B. subtilis and P. fluorescens with foliar nano Zn application is considered a sustainable strategy for increasing nutrition, growth, productivity and Zn biofortification of wheat in tropical savannah